2016
DOI: 10.1002/ijc.30428
|View full text |Cite
|
Sign up to set email alerts
|

Gene panel sequencing in familial breast/ovarian cancer patients identifies multiple novel mutations also in genes others than BRCA1/2

Abstract: Breast and ovarian cancer (BC/OC) predisposition has been attributed to a number of high-and moderate to low-penetrance susceptibility genes. With the advent of next generation sequencing (NGS) simultaneous testing of these genes has become feasible. In this monocentric study, we report results of panel-based screening of 14 BC/OC susceptibility genes (BRCA1, BRCA2, RAD51C, RAD51D, CHEK2, PALB2, ATM, NBN, CDH1, TP53, MLH1, MSH2, MSH6 and PMS2) in a group of 581 consecutive individuals from a German population … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
58
2
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(81 citation statements)
references
References 34 publications
10
58
2
4
Order By: Relevance
“…High throughput NGS‐based multiple gene panel analyses are routinely used for genetic risk assessment in HBOC. Several studies have confirmed the suitability of the commercially available TSCP for HBOC diagnostics . In our study, we performed a systematic screen for PVs in 94 cancer predisposing genes via NGS and CGH.…”
Section: Discussionmentioning
confidence: 70%
“…High throughput NGS‐based multiple gene panel analyses are routinely used for genetic risk assessment in HBOC. Several studies have confirmed the suitability of the commercially available TSCP for HBOC diagnostics . In our study, we performed a systematic screen for PVs in 94 cancer predisposing genes via NGS and CGH.…”
Section: Discussionmentioning
confidence: 70%
“…According to a previous study, the mutation prevalence of BRCA1/2 in Han Chinese patients with early‐onset or familial breast cancer was 15.0% and a 7.5% mutation rate of non‐ BRCA genes was found in women who tested negative for BRCA1/2 mutations (Lin et al., ). In another study of German breast cancer patients, extended testing beyond BRCA1/2 also identified a deleterious mutation in a further 6% of patients (Kraus et al., ). Therefore, although BRCA1/2 genes were the most important susceptibility genes in breast cancer, multiple gene sequencing significantly increased the detection rate of possible disease‐causing mutation carriers.…”
Section: Discussionmentioning
confidence: 99%
“…The technical validity of gene-panel/NGS in comparison with the reference technology was thoroughly assessed in different studies [29,36,42,66,67,68,69,70]. In particular, one of these assessed the sensitivity and specificity of NGS compared with standard Sanger sequencing and MLPA (multiplex ligation-probe amplification) and also confirmed the performance of three different panel designs for HBOC (Custom Design by Castera et al [29]: Table 1 and Table 2).…”
Section: Inherited Cancer Syndromesmentioning
confidence: 99%